Mapping intracellular NAD content in entire human brain using phosphorus-31 MR spectroscopic imaging at 7 Tesla - Guo, Rong; Yang, Shaolin; Wiesner, Hannes M.; Li, Yudu; Zhao, Yibo; Liang, Zhi-Pei; Chen, Wei; Zhu, Xiao-Hong (Frontiers in Neuroscience, 2024)
Nicotinamide adenine dinucleotide (NAD) is a crucial molecule in cellular metabolism and signaling. Mapping intracellular NAD content of human brain has long been of interest. However, the submillimolar level of cerebral NAD concentration poses significant challenges for in vivo measurement and imaging. In this study, we demonstrated the feasibility of non-invasively mapping NAD contents in entire human brain by employing a phosphorus-31 magnetic resonance spectroscopic imaging ( 31 P-MRSI)-based NAD assay at ultrahigh field (7 Tesla), in combination with a probabilistic subspacebased processing method. The processing method achieved about a 10-fold reduction in noise over raw measurements, resulting in remarkably reduced estimation errors of NAD. Quantified NAD levels, observed at approximately 0.4 mM, exhibited good reproducibility within repeated scans on the same subject and good consistency across subjects in group data (2.3 cc nominal resolution). One set of higher-resolution data (1.0 cc nominal resolution) unveiled potential for assessing metabolic tissue heterogeneity, showing similar NAD distributions in white and gray matter. Preliminary analysis of age dependence suggests that the NAD level decreases with age. These results illustrate favorable outcomes of our first attempt to use ultrahigh field 31 P-MRSI and advanced processing techniques to generate a whole-brain map of low-concentration intracellular NAD content in the human brain.